The impact of the state of Ohio stay-at-home order on non-COVID-19 intensive care unit admissions and outcomes - Abi Fadel, Francois; Al-Jaghbeer, Mohammed; Kumar, Sany; Griffiths, Lori; Wang, Xiaofeng; Han, Xiaozhen; Burton, Robert (Anestezjologia Intensywna Terapia, 2020)
Dear Editor, Hospitals reported a decline in emergency room (ER) visits, hospitalisations, and elective procedures during the coronavirus disease 2019 (COVID-19) pandemic [1–4]. This raised concerns over delays in seeking care [5].